2015
DOI: 10.1038/jid.2015.139
|View full text |Cite
|
Sign up to set email alerts
|

Aurora Kinase A Is Upregulated in Cutaneous T-Cell Lymphoma and Represents a Potential Therapeutic Target

Abstract: Cutaneous T-cell lymphomas (CTCLs) form a heterogeneous group of non-Hodgkin's lymphomas characterized by only poor prognosis in advanced stage. Despite significant progress made in the identification of novel genes and pathways involved in the pathogenesis of cutaneous lymphoma, the therapeutic value of these findings has still to be proven. Here, we demonstrate by gene expression arrays that Aurora kinase A is one of the highly overexpressed genes of the serine/threonine kinase in CTCL. The finding was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 37 publications
2
25
0
1
Order By: Relevance
“…44 We also showed that sorted CD8 1 T cells have engraftment properties (Figure 4D-E; data not shown) and that recipients transplanted with Ts1Rhr-Jak3 A572V donor cells mostly develop CD8 1 T-cell expansion, indicating that increased dosage of trisomic genes located in the DSCR functionally cooperate with mutant JAK3 to maintain this phenotype. Because gain of chromosome 21 is found in 7% to 10% of human CTCLs, 16,43 we reanalyzed the transcription profiles of human CTCL samples 45 and observed that both ETS1 and FLI1 (2 Ets-related transcription factors homologous to Ets2 and Erg contained in the DSCR 34 ) were overexpressed 3.17-fold and 3.57-fold, respectively (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…44 We also showed that sorted CD8 1 T cells have engraftment properties (Figure 4D-E; data not shown) and that recipients transplanted with Ts1Rhr-Jak3 A572V donor cells mostly develop CD8 1 T-cell expansion, indicating that increased dosage of trisomic genes located in the DSCR functionally cooperate with mutant JAK3 to maintain this phenotype. Because gain of chromosome 21 is found in 7% to 10% of human CTCLs, 16,43 we reanalyzed the transcription profiles of human CTCL samples 45 and observed that both ETS1 and FLI1 (2 Ets-related transcription factors homologous to Ets2 and Erg contained in the DSCR 34 ) were overexpressed 3.17-fold and 3.57-fold, respectively (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Aurora kinase A (AURKA) is associated with tumorigenesis [84]. Wakahara et al have reported that EWS-FLI1 upregulates the levels of Aurora kinase A and B by directly binding to their promoter regions [85].…”
Section: Targeted Therapymentioning
confidence: 99%
“…Thus as foretold, IL-2 and IL-15 appear to operate in the same pathway in MAC-1 cells. The analysis of CTCL patient biopsies [28] further showed upregulation of genes that are subject to IL-2 mediated upregulation in MAC-1 cells and associated with aggressive phase (MAC-2A) expression profiles, revealing overall upregulation of IL15, JAK3, SOCS1 and TNFRSF9 or CCL17, IFN-gamma, IL17A/F, IL21, IL22, IL6 and IL9 in some patients (Supplementary Figure 3). In contrast to IL-2, IL-15 is produced in the skin and may therefore be more pathologically relevant [29].…”
Section: Resultsmentioning
confidence: 99%